KEGIATAN FISIOTERAPI PADA LANSIA DI GRIYA KHUSNUL KHATIMAH - Sri Sunaringsih Ika Wardojo; Rakhmad Rosadi (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
At Griya Khusnul Khatimah, the community services is provided through a variety of activities, including blood pressure health checks, exercise therapy, and caregiver counseling. The method is to check the blood pressure of the elderly as a source of data for giving interventions, after which carers are counseled on the treatments to be offered. A pre-test and post-test were conducted to determine the effectiveness. Counseling seeks to help caregivers understand the benefits of fitness treatment for the elderly in order to prevent the risk of blood pressure worsening and problems. Counseling seeks to help caregivers understand the benefits of fitness treatment for the elderly in order to prevent the risk of blood pressure worsening and problems. After being given literature about the meaning, advantages, and dosage of Fast Walking Exercise, counseling went well and was easily comprehended by caregivers from 0% to 100%. Counseling activities can help caregivers learn more about exercise therapy for the elderly with hypertension and how to practice Brisk Walking Exercise with the elderly.